Crowdfunding: features, trends and ways of development in modern Russia - V. B. Bulatova (Вестник университета)
The article presents the results of a study of the Russian crowdfunding market, within the framework of which reveals the content of the concept of “crowd finance”, describes the main segments - crowdfunding, crowdlanding and crowdinvesting. The paper analyses the structure of the crowdfunding ecosystem in Russia, identifies its specific features. Based on the analysis of the industry legislation, the study reveals the problematic points, justifies the need for introducing appropriate adjustments. According to the results of the study, the author proves the need for further development of crowd technologies in the domestic financial market, primarily due to the improvement of external conditions and regulatory mechanisms. The paper used the following scientific methods and approaches: observation, comparison, generalization, analysis, logical and system-structural approaches.